Breaking silos: Towards effective integration of humanitarian and resilience programmes in the Horn of Africa - Mohamed, Tahira Shariff (Jameel Observatory for Food Security Early Action, 2024)
Presented at Jameel Observatory for Food Security Early Action Community of Practice meeting, Nairobi, 14-15 May 2024